Zorotypus asymmetricus sp. nov. from Brunei Darussalam, Borneo (Insecta: Zoraptera) - Kočárek, Petr; Wahab, Rodzay Abdul; Kahar, Siti Rafhiah Abdul (Zootaxa, 2017)
A new species of Zoraptera from Borneo is described and figured. Zorotypus asymmetricus sp. nov. was discovered in lowland mixed dipterocarp forest in Ulu Temburong, Brunei Darussalam. The species represents the third known species occurring on Borneo and it can be easily distinguished from others by the asymmetrical cerci: the right cercus is strongly enlarged and curved.